Biodiversity and Conservation of Fruit Crops with their Wild Relatives: A Review (London Journal of Research In Science: Natural and Formal, 2025)
The conservation of biodiversity within fruit crops is essential for sustaining both ecological and agricultural systems. Fruit crops, as integral components of nature's orchard, play a pivotal role in global food security and ecosystem health. India is one of the 12 mega biodiversity centres with 2 biodiversity hotspots which are the reservoirs of plant genetic resources. India stands at 7thplace in the global agricultural biodiversity status. Among fruit and nut crops, there are about 117 cultivated species with 175 wild relatives of which only 25 species have been domesticated. Genetic resources conservation of fruit trees is intricate and complex as they are belonging to various genera and species which require specific climate. Hence, in situ and ex situ conservation can go simultaneously. The western ghat and North eastern India are centres of diversity for several important native fruits including Mango, Jackfruit and Citrus. Apart from the major fruit crops, India is home to several underutilized fruit crops. However, due to increased pressure on land use several of the wild types, which are a great source of genes governing useful traits, are disappearing. Thus, there is an urgent need to conserve them in both in situ and ex situ conditions. The genetic diversity and modes of conservation of tropical fruits are discussed in this paper.
Keywords: propensity score matching; Esophageal cancer risk factors; Synergistic carcinogenesis; Alcohol-tobacco interaction; Case-control study; conservation; GIS; Ex-Situ; Fruits; Germplasm; In- Situ; Tropical; Varieties and Wild species.